Varicose veins and their management. Issue 4 (April 2016) - Bootun, Roshan; Onida, Sarah; Lane, Tristan R.A.; Davies, Alun H.
Abstract: Varicose veins are a common condition, affecting up to a quarter of the UK population. They have been shown to negatively impact on patients' quality of life and are an important cause of morbidity. The treatment of varicose veins has, in turn, been shown to improve the quality of life of patients. Traditional techniques of saphenofemoral and saphenopopliteal junction ligation with or without vein stripping have been the mainstay of treatment for a long time. However, over the past 15 years, day-case minimally invasive endovascular interventions carried out under local anaesthetic have gradually replaced surgical methods. Nowadays, the majority of procedures are carried out using one of the endothermal ablation techniques (radiofrequency ablation [RFA] or endovenous laser ablation [EVLA]). However, these endothermal methods are often associated with discomfort as well as complications due to the use of heat energy. Recently, newer non-thermal, non-tumescent (NTNT) ablation techniques have been launched with the promise of similar effectiveness, but with less pain. This article discusses epidemiology, diagnosis and management of varicose veins, including the latest endovascular and targeted open surgical techniques.